A Comparative Study of Antibacterial Potential of Various Extracts of Different Parts of Jatropha Curcas Linn against Bacterial Strains: Life Sciences-Biochemistry for better diagnosis and therapy - M. Siva Ganesh; Dr. N. Agnel Arul John; Dr. J. Radhika (International Journal of Life Science and Pharma Research, 2022)
Herbal medicines derived from plant extracts are being increasingly utilized to treat a wide variety of clinical diseases, mainly in developing countries for primary health care because of better cultural acceptability, better compatibility with the human body and fewer side effects. Natural medicinal plants having various secondary metabolites such as flavonoids, alkaloids, phenol, terpenoids etc and these have rich medicinal value such as anti-oxidant and anti- microbial activities. Since time immemorial, medicinal plants are widely used for the treatment of different infectious diseases. Infectious diseases caused by bacteria strains have a large impact on public health. Now a days multiple drug resistance has developed due to the indiscriminate use of commercial anti-microbial drugs and impairs the treatment of infectious disease. The present study was focused on the different parts of Jatropha curcas Linn. It belongs to the family Euphorbiaceae , a large deciduous soft wooded shrub 3-4 m in height with sticky juice. The leaf part of the plant is used as galactagogue, lactagogue, rubefacient and have insecticidal properties and they are useful in foul ulcers, tumors and scabies. Seed of the plant is mainly used for dysentery, urinary discharge, abdominal complaints anaemia, fistula and diseases of the heart. The present investigation was carried out to study the antibacterial activity and evaluated for chloroform, methanol and diethyl ether extracts of various parts of Jatropha curcas Linn against Escherichia coli, Staphylococcus aureus and Aeromonas species by disc diffusion method. Based on the zone of inhibition, the antibacterial potential of different parts of the plant viz. leaves, stems and seeds were analysed. The evaluation of various solvent extractions revealed the effectiveness of the antibacterial activity of the plant. Among the various extracts, leaves, stems and seeds parts of the plant extracted with chloroform showed maximum zone of inhibition against all the tested bacterial species followed by methanol and diethyl ether. According to our results, the Jatropha curcas L can be considered as a rich source of active compounds with antibacterial activity. This may recommend a new pathway in elucidating a potent natural antibacterial agent.